Design Of SIW Bandpass Filter With 6 Db Offset - Zakaria, Zahriladha; Ahmad, Badrul Hisham (Institute of Electronic & Electrical Engineers (IEEE), 2011)
This paper presents a novel design of SIW bandpass filter based on even- and odd-mode predistortion technique. This technique allows for the realization of lossy filter responses equivalent to lossless filter responses, although at an increased insertion and return loss. Hence, the filter can be designed with low Qu resonators, which will significantly contribute to the reduction of its physical size and weight. An eexperimental third degree filter with Chebyshev characteristic demonstrated good measured results, which were in-line with the simulated results.